Study of safety management & professional to achive zero accidents in construction site - Mohd Illahi, Mohd Ashri (2010)
Safety management & Safety Professional cannot be separate due to ensure all activity on site is doing safely in term of environmental, hazard and accident on site. The most serious factor accident on site is identifying by the 16 type of factor. The purpose of study is to identify concept of construction safety management and the roles and responsibilities of the safety professionals to prevent accidents and deaths during construction site. 100 of survey questionnaires that were mailed to local construction company which is located in Kuala Lumpur and Selangor. The purpose of the questionnaire is obtain the factor influencing site safety, the importance of safety management, position and disciplines in the safety profession, and safety professionals roles and responsibilities. The analysis can be categorized under two method which is descriptive statistic method and secondly the inferential statistic method or bivariate statistical analysis.